Analysis Of Potential Hazards And Ergonomic Risks During Manual Handling Activities In The Medical Equipment Warehouse Of Pelabuhan Ratu Regional General Hospital - Dian Permana (International Journal of Health Engineering and Technology, 2026)
Logistics management activities in hospitals have complex work characteristics and often involve intensive physical workloads. This study aims to identify potential ergonomic hazards, analyze risk levels, and formulate risk control recommendations for manual material handling (MMH) activities at the Medical Devices Warehouse Installation of RSUD Pelabuhan Ratu. The implementation methods utilized during this residency included direct field observations and structured interviews with warehouse staff. The root cause analysis was qualitatively conducted using a fishbone diagram with 4M+1E parameters (man, method, material, machine, environment) , followed by problem prioritization using the USG (Urgency, Seriousness, Growth) method and intervention strategy formulation through SWOT analysis.  The assessment findings revealed significant potential ergonomic risks due to piles of large and heavy medical equipment being handled manually without mechanical lifting equipment (such as forklifts or hand stackers). Limitations in narrow storage spaces, the absence of OSH (Occupational Safety and Health) signages, and the lack of a specific recording system for musculoskeletal disorders (MSDs) further aggravated the risk level. Based on the USG matrix, the most urgent primary issues are the high intensity of manual heavy lifting and the low awareness among employees regarding proper ergonomic working postures. The SWOT analysis positioned the organization in Quadrant I (Aggressive Strategy). Consequently, the SO (Strength-Opportunity) strategy is recommended to optimize management support by developing an integrated manual handling system with the hospital's OSH programs, conducting regular training and socialization on proper lifting techniques, installing educational OSH signs, and strengthening progressive supervision and evaluation to minimize musculoskeletal injuries among warehouse workers.